2005
DOI: 10.1073/pnas.0508537102
|View full text |Cite
|
Sign up to set email alerts
|

The asialoglycoprotein receptor clears glycoconjugates terminating with sialic acidα2,6GalNAc

Abstract: Endogenous ligands have not, to date, been identified for the asialoglycoprotein receptor (ASGP-R), which is abundantly expressed by parenchymal cells in the liver of mammals. On the basis of the rapid clearance of BSA bearing multiple chemically coupled sialic acid (Sia)␣2,6GalNAc␤1,4GlcNAc␤1,2Man tetrasaccharides (SiaGGnM-BSA) from the circulation, and the ability of the ASGP-R hepatic lectin-1 subunit to bind SiaGGnM-BSA, we previously proposed that glycoproteins modified with structures terminating with Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 36 publications
2
103
0
Order By: Relevance
“…35 Since mouse ASGPR also seems to bind to a2,6-sialylated glycans in addition to ß-linked galactose and N-acetylgalactosamine, the human a2,3-sialyltransferase ST3GAL4 -and not an ST6GAL1 -was selected for increasing the level of antibody sialylation. 36,37 In contrast, in human serum IgA1 more than 95% of sialic acids were linked in the a2,6-configuration.…”
Section: Her2mentioning
confidence: 98%
“…35 Since mouse ASGPR also seems to bind to a2,6-sialylated glycans in addition to ß-linked galactose and N-acetylgalactosamine, the human a2,3-sialyltransferase ST3GAL4 -and not an ST6GAL1 -was selected for increasing the level of antibody sialylation. 36,37 In contrast, in human serum IgA1 more than 95% of sialic acids were linked in the a2,6-configuration.…”
Section: Her2mentioning
confidence: 98%
“…Sialic acid can be linked to the galactose either with α2,3 or α2,6 linkage. Recent studies showed that α2,3 sialylation provides a better protection to the protein than α2,6 sialylation, as ASGPR recognizes Siaα2,6Gal and Siaα2,6GalNAc moieties in addition to the well-known Gal and GalNAc residues [14,15]. However, Fc-glycans have no apparent impact on IgG half-life [16].…”
Section: Sialic Acids In Fc N-glycansmentioning
confidence: 99%
“…[15][16][17] For example, asialoglycoprotein receptors are located on liver cancer cells and can specifically bind with glycoprotein on/in galactose residues, leading to internalization and subsequent degradation of glycoprotein inside the cells. 18 Such active targeting strategies can not only effectively deliver drugs into cancer cells, but also reduce the amounts of anticancer agents used.…”
Section: Introductionmentioning
confidence: 99%